ANALISIS PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN PADA KANTOR CAMAT POMALAA - Layuk, Ririn Yudhani; Triani, Neks; Nichen, Nichen (Komunitas Manajemen Kompetitif, 2025)
The purpose of this study is to determine the adequacy of the implementation of government accounting in the Pomalaa Subdistrict Office.This study uses a qualitative approach with a descriptive method, conducted at the Pomalaa Subdistrict Office. Data collection was conducted through observations, interviews, and documentation. The data analysis techniques employed were data reduction, data presentation, and conclusion-making. The main informants for the study were the Treasurer and the Head of Planning and Finance of the Pomalaa Subdistrict Office. The results of this study indicate that the Pomalaa Subdistrict Office has implemented an accrual-based cash accounting system, which includes the preparation of financial reports such as Budget Execution Reports, Balance Sheets, Operating Reports, Reports on Changes in Equity, and Notes to Financial Statements, in accordance with the mandate of the Government Accounting Standards (SAP), as stipulated in Government Regulation No. 12 of 2019. However, implementation obstacles remain, such as the lack of separation of daily records between cash inflows and outflows and the lack of daily adjustment records for fixed assets. Furthermore, the use of supporting applications such as SIPD, e-Sakip, and e-Monev still presents technical obstacles. Overall, however, the implementation of accounting at the Pomalaa Subdistrict Office complies with regulations and can be the basis for increasing accountability and transparency in regional financial management. Keywords: Government Accounting, SAP, Financial Reporting, sub-districts, Government Regulation No. 12 of 2019.